E-five mart / Aisyah Lod ...[et al.] - Lod, Aisyah; Hamdan, Hani Nurina; Kharil Bahri, Nur Rashidah Izzati; Raja Badarudin, Raja Bismi Athirah; Syed Fahmey Sham, Syed Hafiz Ashraf (2023)
E-Five Mart will be the first to offer smart supermarket services in Malaysia. The idea behind this business is to offer new experiences for people to grocery shop. E-Five Mart is not the typical supermarket you can find at other places. It has its own uniqueness and technological advancement which makes this smart supermarket special and has its own competitive advantage. The business is conducted in an urban area which is located at Shah Alam, Selangor. The target market is to all individuals regardless of their ages since it is a supermarket, a place for all. However, E-Five Mart expects more consumers from M40 and T20 groups to shop at this supermarket because the price of grocery products at E-Five Mart will be slightly higher compared to other regular supermarkets. This is due to the fact E-Five Mart operated twenty- four hours daily. Social Media will be the top platform for E-Five Mart to promote its business. In addition, E-Five Mart is a business that incorporates problem solving and innovation in its key activities. This is because this smart supermarket will put an end to the biggest frustration which is queueing in the long line at the cashier. In today's world, all supermarkets, whether big or small, follow the same concept. However, the retail needs are evolving from time to time. Hence, E-Five Mart responds to this problem by grabbing the opportunity to run this business that will cater supermarket problems which still exist in the community with the help of technology such as smart trolleys. Last but not least, E-Five Mart is believed to thrive in the future and always will be demanded by people and it is important for us to make this dream come true